REVIEW OF CT COLONOGRAPHY: REAL-LIFE EXPERIENCE OF ONE THOUSAND CASES IN A TERTIARY REFERRAL CENTRE. (8th June 2013) - Smyth, A E; Healy, C F; MacMathuna, P; Fenlon, H M
Abstract : Introduction: CT Colonography is increasingly being utilised to investigate patients with lower gastrointestinal symptoms and in screening for colorectal carcinoma in the at risk population. Aims/Background: This review aimed to quantify results from a real life experience of 1000 CT Colonography examinations in a tertiary referral hospital campus. Method: Data on patient demographics, indications and findings were analysed retrospectively from a dedicated database. Results: Over a five year period (January 2008–December 2012) 1000 CT Colonography examinations were performed. The median age was 70 years (IQR 60–79). Patients were symptomatic in 86% of cases, screening accounted for 7% and surveillance in patients with a history of polyps or colorectal cancer for 7%. In 45% of patients it was documented that the study was performed following an incomplete optical colonoscopy. CT Colonography had normal or benign colonic findings in 75% of patients. 6% had incomplete examinations performed. Neoplasia was observed in 14%: colorectal carcinoma 6%, polyps >1cm in 3% and 5% were found to have <3 polyps of 6–9 mm. 5% had findings of wall thickening or strictures that were suspected to be benign but required further endoscopy and biopsy. There was an extracolonic finding that required further evaluation in 19% with 6% found to have a potentially clinically significant finding. There were no significant procedure related complications. Conclusion: This review describes the real life experience of CT Colonography in a largely elderly, symptomatic patient group. In this patient group, CT Colonography safely confirmed the need for no further bowel tests in 75%, identified colorectal cancer in 6% and clinically significant extracolonic findings in 6% of cases without any significant complications.